Pengaruh Kadar Gula dan Suhu terhadap Kandungan Gula di dalam Telur Ayam Ras Setelah Perendaman di Larutan Gula - Aisah, Mutiara Nur; Tamrin, Tamrin; Amin, Muhammad; Kuncoro, Sapto (abe.fp.unila.ac.id, 2022)
Making sweet chicken eggs using a sugar solution takes 5 days. This study aims to study the effect of the concentration of the sugar solution and the immersion temperature level on the sugar content in broiler eggs after soaking. This study was designed using a Factorial Completely Randomized Design (CRD) consisting of 2 factors, namely the concentration of sugar solution (15%, 20%, and 25%) and temperature (40 oC, 50 oC, 60 oC, and 70 oC) respectively. Based on this research, each treatment was soaked for 120 hours and repeated three times. The results of this study indicate that the concentration and temperature of immersion affect the sugar content and organoleptic content of sweet chicken eggs. The higher the concentration given, the higher the total sugar content produced in sweet chicken eggs and the higher the immersion temperature, the faster the diffusion of sugar into the eggs. Keywods: diffusion, sugar concentration, Sweet egg, temperature.